Polarised photoluminescence from oriented polymer liquid crystal films - BLAU, WERNER (My University, 1997)
Optical anisotropy in a new form of crosslinked liquid crystal network incorporating a fluorescent chromophore has been demonstrated. Linearly polarised absorption and fluorescence is observed in oriented thin films. From measurement of absorption and fluorescence anisotropy, the order parameter was found to be 0.65 and 0.80, respectively. Temperature dependent birefringence measurements reveal that there is no appreciable loss of alignment up to 200 ?C.
PUBLISHED
Keywords: Optical anisotropy; Optical anisotropy